Hidden in Plain Sight. Politics and Design in State-Subsidized Residental Architecture. - (:unkn) unknown (Park Books, 2021)
Sozialer Wohnungsbau hat in Europa eine weit zurückreichende Tradition. Seit den Anfängen des 20. Jahrhunderts etablieren sich diese oft anonym errichteten und bisweilen verkannten Bauten in den Vororten großer europäischer Städte. Mit dem multidisziplinären internationalen Forschungsprojekt "Mapping Public Housing" spürt das Center for Studies in Architecture and Urbanism der Universität Porto diesem architektonischen Erbe nach und zeigt, dass sich oft lebendige Siedlungen und ganze Stadtteile aus den Wohnbauprojekten herausgebildet haben. Im Buch werden exemplarische Beispiele u. a. aus Deutschland, Großbritannien, Portugal, der Schweiz und Spanien näher angeschaut. Das Spektrum reicht von den Anfängen des sozialen Wohnungsbaus in Portugal dank deutscher Investitionen während des Ersten Weltkriegs über die Propagandapolitik in Zusammenhang mit subventioniertem Wohnen für die Arbeiterklasse der 1940er-Jahre bis hin zu nachhaltigen Konzeptideen für die Zukunft. So entsteht ein breites Panorama, das die Entwicklung des subventionierten Bauens als Teil der Kulturgeschichte Europas versteht und die wichtige Rolle nachzeichnet, die dem staatlich alimentierten Wohnungsbau bei der Entstehung des europäischen Wohlfahrtstaats zukam.

Social housing has a long tradition in Europe. Since the early 20th century, these often anonymously built and unappreciated structures have arisen all across the suburbs of Europe's major cities. In the multidisciplinary and international research project Mapping Public Housing, the Center for Studies in Architecture and Urbanism at the University of Porto's Faculty of Architecture has been tracing the architectural heritage of social housing. The findings demonstrate that, in many cases, vibrant neighbourhoods and entire city districts have emerged from such social housing programs. This book takes a closer look at exemplary developments in Germany, Great Britain, Portugal, Switzerland, and Spain. The case studies cover a wide range of social and historical contexts, from the beginnings of social housing in Portugal sparked by German investment during World War I to the propaganda policies associated with subsidised housing for the working class in the 1940s, and to sustainable concepts and ideas for the future. Hidden in Plain Sight offers a wide-ranging panorama that recognises the development of subsidised residential construction as a part of Europe's cultural history and traces the important role that state-funded housing has played in the emergence of the European welfare state.
Keywords: Wohnungsbau; Sozialer Wohnungsbau; Sozialwohnung; Stadtplanung; Kommunale Wohnungspolitik; Subvention; Internationaler Vergleich; Kulturgeschichte; Sozialgeschichte